2017
DOI: 10.1186/s12974-017-0975-6
|View full text |Cite
|
Sign up to set email alerts
|

Withania somnifera as a potential candidate to ameliorate high fat diet-induced anxiety and neuroinflammation

Abstract: BackgroundThe epidemic of obesity has reached alarming levels in both developing and developed nations. Excessive calorie intake and sedentary lifestyle due to technological advancements are the main causal factors for overweight and obesity among the human population. Obesity has been associated with a number of co-morbidities such as hypertension, type 2 diabetes mellitus, cardiovascular diseases, and neurodegeneration and dementia. The progression of neurological disorders in obese subjects has been mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 63 publications
1
17
1
Order By: Relevance
“…Our results also discard a potential diet-associated neuroinflammation factor in these observed long-term alterations, despite previous reports suggesting that a hypercaloric diet might result in neuroinflammation, thus contributing to behavioral disorders [ 40 , 45 ]. Our results do not support this hypothesis, since we did not find alterations in the mRNA expression of several genes that would indicate the activation of inflammatory pathways, such as the toll-like receptor related to pathogen recognition and the activation of innate immunity Tlr4 , the cyclooxygenase key in prostaglandin biosynthesis Ptgs2 , the microglia/macrophage-specific calcium-binding protein Iba1 , the major intermediate filament proteins of mature astrocytes Gfap , and the cannabinoid receptor Cnr2 , induced by the perinatal and/or postnatal P diet in the adult offspring PFC.…”
Section: Discussioncontrasting
confidence: 87%
“…Our results also discard a potential diet-associated neuroinflammation factor in these observed long-term alterations, despite previous reports suggesting that a hypercaloric diet might result in neuroinflammation, thus contributing to behavioral disorders [ 40 , 45 ]. Our results do not support this hypothesis, since we did not find alterations in the mRNA expression of several genes that would indicate the activation of inflammatory pathways, such as the toll-like receptor related to pathogen recognition and the activation of innate immunity Tlr4 , the cyclooxygenase key in prostaglandin biosynthesis Ptgs2 , the microglia/macrophage-specific calcium-binding protein Iba1 , the major intermediate filament proteins of mature astrocytes Gfap , and the cannabinoid receptor Cnr2 , induced by the perinatal and/or postnatal P diet in the adult offspring PFC.…”
Section: Discussioncontrasting
confidence: 87%
“…Various experimental and clinical studies have reported memory enhancing and learning improvement potential of alcoholic and water based formulation of Ashwagandha [52]. Recently our lab reported that aqueous extract of Ashwagandha has immunomodulatory and anxiolytic effects and improved memory retention and learning ability by alleviating cellular stress via regulating synaptic plasticity and cell survival signaling cascades in acute sleep deprived and HFD fed obese rats [32, 33, 35, 53].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, similar antioxidant and anti-inflammatory effects have been reported for luteolin in diabetic mice [120]. Other studies in prediabetic models have shown a protective role for Withania somnifera , which may reduce gliosis and microgliosis as well as expression of inflammation markers such as PPARγ, iNOS, MCP-1, TNF-α, IL-1β, and IL-6 [121]. In line with these observations, oral administration of an hexanic extract of Eryngium carlinae inflorescences to diabetic rats not only reduced glucose levels but also limited overall oxidation, by reducing lipid peroxidation, protein carbonylation and reactive oxigen species production, while increasing catalase activity in the brain [122].…”
Section: Natural Compounds and Central Complications In Dmmentioning
confidence: 53%